Developing a capacity-building intervention for healthcare workers to improve communication skills and awareness of hard of hearing and D/deaf patients: results from a participatory action research study - Véronique S. Grazioli; Madison Graells; Elodie Schmutz; Odile Cantero; Tanya Sebaï; Vanessa Favre; Jessica Richème-Roos; Kevin Morisod; Michel Jeanneret; Pascal Singy; Patrick Bodenmann (BMC, 2024)
Abstract Background Healthcare workers (HCWs) are commonly not prepared to properly communicate with D/deaf and hard of hearing (HoH) patients. The resulting communication challenges reinforce the existing barriers to accessing and benefiting from quality of care in these populations. In response, this study aimed to develop and evaluate a capacity-building intervention for HCWs to raise their awareness of D/deaf and HoH individuals' experiences in healthcare and improve their capacity to communicate with these populations. Methods This study featured a participatory action research design using qualitative and quantitative methods. The intervention was developed and tested through 4 iterative phases. Reactions (i.e., satisfaction and perception of the intervention content, quality, appropriateness and usefulness) were assessed quantitatively and qualitatively after the intervention, whereas perceived knowledge and self-efficacy in communicating with D/deaf and HoH patients and organizational payoffs (use frequency of basic rules and tools improving communication) were quantitatively assessed before, after and 6-month post-intervention. Results Main qualitative and quantitative findings showed that the final version of the intervention reached high levels of satisfaction among participants. Next, perceived knowledge and self-efficacy scores obtained after receiving the intervention and 6 months later were significantly higher than those yielded in the initial assessment, although both scores significantly decreased at 6 months (compared to the scores obtained just after the intervention). Finally, findings showed no significant changes in organizational payoffs after receiving the intervention. Echoing these results, main qualitative findings documented that after receiving the intervention, participants felt more confident yet not more equipped to communicate with D/deaf and HoH patients. Conclusions Findings suggest that the capacity-building intervention is a promising means to sustainably increase HCWs' perceived knowledge and self-efficacy on how communicating with D/deaf and HoH patients, although complementary approaches and follow-up intervention reminders may be necessary to enable practice changes in the working environment.